Dispositional Employability and Online Training Purchase. Evidence from Employees' Behavior in Spain - Torrent-Sellens, Joan; Ficapal-Cusí, Pilar; Boada-Grau, Joan (Frontiers in Psychology, 2016)
This article explores the relationship between dispositional employability and online training purchase. Through a sample of 883 employees working for enterprises in Spain, and a using principal component analysis and binomial logit probabilistic models, the research revealed two main results. First, it was found that dispositional employability is characterized by five factors: “openness to changes at work”, “career motivation and work resilience”, “work and career proactivity”, “optimism and engagement at work”, and “work identity”. Second, the research also found a double causality in the relationship analysis between dispositional employability and online training purchase. However, this causality is not direct. In explaining dispositional employability, certain motivations and types of behavior of employees participating in online training are significant. In particular, greater sensitivity towards career-related personal empowerment, a greater predisposition towards developing new experiences at work, and a greater awareness of the fact that positive job outcomes are related to preparation conscientiousness. In explaining online training purchase, employees who are more motivated and who better identify with their jobs are more likely to pay. Moreover, employees who spend more time on training and have less contact with new trends in their jobs, find it hard to keep calm in difficult situations, and have a greater predisposition towards effort, and preference for novelty, variety and challenges at work are more likely to purchase online training.